Orchidectomy enhances the expression of endothelin-1 and ETB receptors in rat portal vein - Rossignoli, Patrícia de Souza [UNESP]; Labio, Roger Willian de; Payão, Spencer Luiz Marques; Pereira, Oduvaldo Câmar Marques [UNESP]; Chies, Agnaldo Bruno (Japan Society of Smooth Muscle Research, 2014)
Functional studies have shown that orchidectomy increases the effects of phenylephrine on rat portal veins, but that it is completely prevented in the presence of both ETA and ETB receptor antagonists. Although it suggests the involvement of endothelin-1 (ET-1), the local production of this vasoactive peptide has not been directly quantified in portal veins. Therefore, the aim of the present study was to verify if orchidectomy increases the local expression of ET-1 as well as ETA and ETB receptors in the rat portal vein. Indeed, the genic expression of ET-1, ETA and ETB receptors in rat portal veins taken from control (CONT), orchidectomized (ORX) and ORX plus testosterone-replacement therapy (ORX + T) animals were determined by Real Time RT-PCR. The results showed that orchidectomy induced a significant increment in genic expression of ET-1and ETB receptors in the rat portal veins, which was completely reversed by testosterone replacement treatment. In conclusion, the results suggest that orchidectomy increases the production of ET-1 in the rat portal vein and that, at least partially, it may be related to the previously reported elevation of responses to phenylephrine.
Keywords: Endothelin-1; ETB receptor; Orchidectomy; Portal vein; Testosterone